7. Density of Lumbal Vertebrae Bone Ovariectomized Rat (Rattus Norvegicus) Given the Extract Sipatah – patah ( Cissus quadrangularis Salisb ) - Putri Dewi; Mustafa Sabri; Erdiansyah Rahmi; M Jalaluddin; Nuzul Asmilia; Al Azhar (Universitas Syiah Kuala, 2017)
The aims of this research was to determine the density level of lumbal vertebrae on ovariectomized rats administered with Cissus qudrangula Salisb stem extract with various doses. In this research twelve female rats were randomizedly divided into 4 groups with 3 treatment repetition. K1-groups were ovariectomized rats without Cissus quadrangula Salisb trunct extract administration; K2, K3, and K4, were ovariectomized and given with Cissus quadrangula Salisb extract with 500 mg/kg/Bw, 700 mg/kg/Bw, and 900 mg/kg/Bw as doses perday for 30 days. On day-31, rats were euthanized using chloroform and the os lumbal-5 were collected, followed with histological preparations. Research parameters were the density of active osteoblasts, passive osteoblasts, and osteoclasts. The results showed that the damage in K1 was clearly marked with the high number of osteoclasts, K2 and K3 indicate lower osteoclasts levels than K1 and had repaired bone structure characterized with active cuboidal shaped osteoblast activity and passive flat shaped osteoblasts and K4 showed increasing level of active osteoblasts. The administration of Cissus quadrangula Salisb stem extract at 900 mg/kg/bw for 30 days showed bone repair due to ovariectomy indicated with high level of active osteoblasts.